Micro-arc oxidation electrolyte and magnesium alloy surface treatment method

By using optimized microarc oxidized electrolyte and DC pulse power supply technology, a uniform nanosheet structural film layer on the surface of magnesium alloy is formed at low voltage, solving the problems of high energy consumption and uneven film layer in the existing technology, and achieving High-efficiency, low-cost magnesium alloy surface treatment.

CN119433654APending Publication Date: 2025-02-14DONGGUAN UNIV OF TECH +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411560775.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing microarc oxidation technology has problems such as large energy consumption, uneven membrane structure, high cost and environmental pollution under high voltage operation, making it difficult to effectively control the formation and performance of nanosheet structures.

Method used

Using an optimized microarc oxidation electrolyte, including film forming agent, auxiliary film forming agent and additive, microarc oxidation is carried out at a voltage of 50-150V through a DC pulse power supply to control the growth of the oxide film to form a dense and uniform Nanosheet structural membrane layer.

Benefits of technology

It realizes the formation of a uniform nanosheet structural film layer under low voltage conditions, reduces energy consumption and cost, avoids film layer defects and unevenness problems, and improves the corrosion resistance and production efficiency of the magnesium alloy surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005117814980000051
    Figure BDA0005117814980000051
  • Figure BDA0005117814980000052
    Figure BDA0005117814980000052
  • Figure BDA0005117814980000061
    Figure BDA0005117814980000061
Patent Text Reader

Abstract

The invention relates to the technical field of magnesium alloy surface treatment, and discloses a micro-arc oxidation electrolyte and a magnesium alloy surface treatment method. The micro-arc oxidation electrolyte comprises the following components by concentration: 50-200 g / L of a film-forming agent; 20-80 g / L of an auxiliary film-forming agent; 1 to 50 mL / L of an additive; a solvent of the micro-arc oxidation electrolyte is water. The magnesium alloy surface treatment method comprises the following steps: S1, pretreating a magnesium alloy workpiece to obtain a pretreated magnesium alloy sample; and S2, the pretreated magnesium alloy sample serves as an anode, a stainless steel plate serves as a cathode, the pretreated magnesium alloy sample and the stainless steel plate are placed in the micro-arc oxidation electrolyte, and a direct-current pulse power source is adopted for micro-arc oxidation treatment. The micro-arc oxidation electrolyte provided by the invention is simple in composition, the magnesium alloy surface treatment method under the low-voltage condition provided by the invention can form a compact and uniformly-distributed nanosheet structure on the magnesium alloy surface, the preparation process is simplified, and the production efficiency is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloy surface treatment, and in particular to a micro-arc oxidation electrolyte and a magnesium alloy surface treatment method. Background Art

[0002] As a lightweight, high-specific-strength metal material, magnesium alloy has broad application prospects in aerospace, automobile manufacturing, electronic equipment and other fields. However, magnesium alloy has high chemical activity and poor corrosion resistance in the environment, which limits its application in more fields. Although traditional magnesium alloy surface treatment methods, such as electroplating and chemical plating, can improve its corrosion resistance to a certain extent, they have problems such as complex process, high cost and environmental pollution.

[0003] In response to the corrosion resistance of magnesium alloys, micro-arc oxidation technology (MAO) has become a hot topic of research in recent years due to its environmental protection, high efficiency and low cost. Micro-arc oxidation technology forms a dense oxide film on the surface of magnesium alloy, effectively isolating the metal matrix from the outside world, and significantly improving the corrosion resistance of magnesium alloy. Although traditional micro-arc oxidation technology can effectively enhance the surface performance of magnesium alloys, it usually requires high voltage operation, high energy consumption and difficulty in accurately controlling the film structure. In order to further optimize the structure and performance of the micro-arc oxidation film, hydrothermal post-treatment technology has been introduced into the micro-arc oxidation process. Hydrothermal post-treatment can not only reorganize the composition of the micro-arc oxidation film, but also form a special nanosheet structure, thereby giving it new physical and chemical properties.

[0004] CN 109989090 A, CN 112458512 A, CN 112458512 A, CN 113638026 A, CN116988120A, CN 114703529 A, CN 117230437 A and CN 118127510 A have successively disclosed methods for preparing micro-arc oxidation-layered double hydroxide (MAO-LDH) composite films by micro-arc oxidation + hydrothermal treatment, and obtained a series of excellent properties, including corrosion inhibition, self-repairing, slow release, super hydrophobicity and super slippery, etc. Although the preparation of nanosheet structures by hydrothermal post-treatment of micro-arc oxidation films has shown significant advantages in improving material properties, it is also accompanied by a series of technical and application-level problems and challenges, mainly including the following aspects:

[0005] (1) During the hydrothermal treatment process, especially under high temperature and high pressure conditions, if the treatment conditions are not properly controlled, the micro-arc oxidation film may crack, peel off or even be completely destroyed, affecting the continuity and integrity of the final nanosheet structure;

[0006] (2) Factors such as non-uniform heating, uneven solution flow, or uneven distribution of reactants during the hydrothermal process may cause uneven formation of nanosheet structures, affecting the consistency and repeatability of material properties;

[0007] (3) Hydrothermal post-treatment usually requires expensive equipment, such as a high-pressure reactor, and long processing cycles and high energy consumption. These factors increase the cost of the entire process and reduce efficiency, becoming an obstacle to industrial application.

[0008] (4) When using specific chemical reagents as hydrothermal media, harmful by-products may be produced, and improper handling may cause environmental pollution. There are also safety issues during the operation.

[0009] Therefore, developing a new method that is simple, efficient, low-energy and can directly generate nanosheet structures on the surface of micro-arc oxidation films has important practical significance and application value. Summary of the invention

[0010] The present invention aims to solve at least one of the above-mentioned technical problems existing in the prior art. To this end, one of the purposes of the present invention is to provide a micro-arc oxidation electrolyte; the second purpose of the present invention is to provide a method for preparing the micro-arc oxidation electrolyte; the third purpose of the present invention is to provide a magnesium alloy surface treatment method; the fourth purpose of the present invention is to provide a magnesium alloy.

[0011] In order to achieve the above object, the technical solution adopted by the present invention is:

[0012] The first aspect of the present invention provides a micro-arc oxidation electrolyte, which comprises the following components in terms of concentration: 50-200 g / L of a film-forming agent; 20-80 g / L of an auxiliary film-forming agent; and 1-50 mL / L of an additive. The solvent of the micro-arc oxidation electrolyte is water.

[0013] Preferably, in terms of concentration, the micro-arc oxidation electrolyte comprises the following components: 70-200 g / L of film-forming agent; 20-60 g / L of auxiliary film-forming agent; 5-15 mL / L of additives; and the solvent of the micro-arc oxidation electrolyte is water.

[0014] Further preferably, in terms of concentration, the micro-arc oxidation electrolyte comprises the following components: 70-180 g / L of film-forming agent; 20-50 g / L of auxiliary film-forming agent; 5-10 mL / L of additives; and the solvent of the micro-arc oxidation electrolyte is water.

[0015] Preferably, the micro-arc oxidation electrolyte provided by the present invention does not contain harmful heavy metal ions.

[0016] Specifically, the micro-arc oxidation electrolyte provided by the present invention does not contain harmful heavy metal ions, and does not generate toxic gases during the preparation and use processes, thereby reducing environmental pollution and meeting environmental protection requirements.

[0017] Preferably, the film-forming agent includes an alkali metal hydroxide; further preferably, the film-forming agent includes at least one of sodium hydroxide and potassium hydroxide.

[0018] Preferably, the auxiliary film-forming agent includes ionic fluoride; more preferably, the auxiliary film-forming agent includes at least one of sodium fluoride, potassium fluoride and ammonium fluoride.

[0019] Preferably, the additive includes a polyol; more preferably, the additive includes at least one of ethylene glycol, propylene glycol, butylene glycol, glycerol, and polyethylene glycol.

[0020] Preferably, the molecular weight of the polyethylene glycol is 200-1000.

[0021] The second aspect of the present invention provides a method for preparing the micro-arc oxidation electrolyte according to the first aspect of the present invention, comprising the following steps:

[0022] The components are mixed to obtain the micro-arc oxidation electrolyte.

[0023] Preferably, the preparation method specifically comprises the following steps: dissolving components including a film-forming agent, an auxiliary film-forming agent and an additive in a solvent to obtain the micro-arc oxidation electrolyte.

[0024] A third aspect of the present invention provides a magnesium alloy surface treatment method, comprising the following steps:

[0025] S1. pretreating a magnesium alloy workpiece to obtain a pretreated magnesium alloy sample;

[0026] S2. Using the pretreated magnesium alloy sample as an anode and a stainless steel plate as a cathode, placing them in the micro-arc oxidation electrolyte described in the first aspect of the present invention, and performing micro-arc oxidation treatment using a direct current power supply.

[0027] Preferably, the magnesium alloy includes one of AZ91 magnesium alloy and AZ31 magnesium alloy.

[0028] Preferably, in step S1, the specific operations of the pretreatment include: grinding and polishing, tap water rinsing, alcohol ultrasonic cleaning, deionized water cleaning and drying. Grease and impurities on the surface of the magnesium alloy workpiece can be removed by pretreatment.

[0029] Preferably, the alcohol ultrasonic cleaning time is 5-15 min; further preferably, the alcohol ultrasonic cleaning time is 5-10 min.

[0030] Preferably, in step S2, the voltage of the micro-arc oxidation treatment is 50-150V.

[0031] Preferably, in step S2, the current density of the micro-arc oxidation treatment is 2-10A / dm 2 Further preferably, the current density of the micro-arc oxidation treatment is 5-10A / dm 2 .

[0032] Preferably, in step S2, the frequency of the DC pulse power supply is set to 0-1000 Hz; further preferably, the frequency of the DC pulse power supply is set to 300-700 Hz.

[0033] Preferably, in step S2, the duty cycle of the DC pulse power supply is set to 0-30%; further preferably, the duty cycle of the DC pulse power supply is set to 10-20%.

[0034] Preferably, in step S2, the temperature of the micro-arc oxidation electrolyte is 10-30°C; further preferably, the temperature of the micro-arc oxidation electrolyte is 15-25°C.

[0035] Preferably, in step S2, the time of the micro-arc oxidation treatment is 5-30 minutes; further preferably, the time of the micro-arc oxidation treatment is 5-15 minutes.

[0036] Preferably, in the step S2, after the micro-arc oxidation treatment is completed, the step of washing and drying the pretreated magnesium alloy sample is also included.

[0037] Preferably, the washing includes washing with flowing deionized water and ultrasonic cleaning by immersion in anhydrous ethanol.

[0038] Preferably, the deionized water cleaning time is 1-5 minutes, and the anhydrous ethanol immersion ultrasonic cleaning time is 3-7 minutes. The residual electrolyte on the surface of the specimen can be removed by washing.

[0039] A fourth aspect of the present invention provides a magnesium alloy, the surface of which has a nanosheet structure film layer formed by the magnesium alloy surface treatment method described in the third aspect of the present invention.

[0040] Preferably, the thickness of the nanosheet structure film layer is less than 100 nm.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The micro-arc oxidation electrolyte provided by the present invention has simple ingredients; the magnesium alloy surface treatment method provided by the present invention effectively controls the micro-arc discharge process, reduces excessive energy consumption, and avoids film defects and non-uniformity problems caused by high voltage by using optimized electrolyte formula and process parameters; the micro-arc oxidation treatment is carried out at a voltage of 50-150V using a DC pulse power supply, and the low voltage condition makes the oxide film grow more uniformly, which is helpful to form a dense and uniformly distributed nanosheet structure on the surface of the magnesium alloy.

[0043] Compared with the traditional multi-step method for preparing a film layer with a nanosheet structure, the one-step magnesium alloy surface treatment proposed in the present invention greatly simplifies the preparation process, improves production efficiency, and ensures the high-quality growth of the nanosheet structure; this nanosheet structure not only increases the specific surface area of ​​the film layer, but also provides more active sites for the magnesium alloy surface, which is conducive to further functional modification such as stearic acid modification, and continues to optimize the performance of the magnesium alloy; this method has a simple process flow, low equipment requirements, and low production cost, which is conducive to the large-scale application and promotion of magnesium alloy surface treatment technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 This is the surface morphology of the micro-arc oxidation film layer of AZ91 magnesium alloy in Example 1;

[0045] Figure 2 This is the surface morphology of the micro-arc oxidation film layer of AZ91 magnesium alloy in Example 2;

[0046] Figure 3 This is the surface morphology of the micro-arc oxidation film layer of AZ31 magnesium alloy in Example 3;

[0047] Figure 4 This is the surface morphology of the micro-arc oxidation film layer of AZ91 magnesium alloy in Comparative Example 1;

[0048] Figure 5 This is the surface morphology of the micro-arc oxidation film layer of AZ31 magnesium alloy in Comparative Example 3;

[0049] Figure 6 The contact angles of the AZ91 magnesium alloy having a nanosheet structure film layer on the surface in Example 1 before (a) and after (b) stearic acid modification;

[0050] Figure 7 The Tafel polarization curves of AZ91 magnesium alloy substrate, AZ91 magnesium alloy with a nanosheet structure film layer on the surface in Example 1, and AZ91 magnesium alloy with a nanosheet structure film layer on the surface in Example 1 modified with stearic acid in 3.5wt% NaCl aqueous solution. DETAILED DESCRIPTION

[0051] The present invention is further described in detail below by specific examples. Unless otherwise specified, the raw materials, reagents or devices used in the examples and comparative examples can be obtained from conventional commercial sources or can be obtained by prior art methods. Unless otherwise specified, the experiments or test methods are conventional methods in the art.

[0052] Example 1

[0053] This embodiment provides a micro-arc oxidation electrolyte and a magnesium alloy surface treatment method. The composition of the micro-arc oxidation electrolyte is shown in Table 1:

[0054] Table 1 Composition of Micro-arc Oxidation Electrolyte in Example 1

[0055]

[0056] The preparation method of micro-arc oxidation electrolyte is as follows:

[0057] After adding a film-forming agent, an auxiliary film-forming agent and additives into deionized water, the mixture is fully stirred until they are completely dissolved to obtain a micro-arc oxidation electrolyte.

[0058] The steps of magnesium alloy surface treatment are:

[0059] S11, polishing the AZ91 magnesium alloy with water-resistant sandpaper, rinsing with tap water, and then ultrasonically cleaning with alcohol for 5 minutes to remove surface grease and impurities, then rinsing with deionized water and drying naturally to obtain a pretreated magnesium alloy sample;

[0060] S21, using the pretreated AZ91 magnesium alloy sample as the anode and the stainless steel plate as the cathode, placed in the electrolyte prepared in S11, turning on the cooling water circulation system, setting the frequency to 500 Hz, the duty cycle to 15%, using a DC power supply, the voltage controlled within 100 V, and the current density to 5 A / dm 2 , micro-arc oxidation treatment at 20°C for 10 min;

[0061] S22. After the micro-arc oxidation is completed, the sample is immediately taken out and placed in flowing deionized water for cleaning for 2 minutes to remove the electrolyte residue. Subsequently, it is immersed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. Finally, it is naturally air-dried at room temperature to obtain an AZ91 magnesium alloy with a nanosheet structure film layer on the surface.

[0062] Example 2

[0063] This embodiment provides a micro-arc oxidation electrolyte and a magnesium alloy surface treatment method. The composition of the micro-arc oxidation electrolyte is shown in Table 2:

[0064] Table 2 Composition of Micro-arc Oxidation Electrolyte in Example 2

[0065]

[0066]

[0067] The preparation method of micro-arc oxidation electrolyte is as follows:

[0068] After adding a film-forming agent, an auxiliary film-forming agent and additives into deionized water, the mixture is fully stirred until they are completely dissolved to obtain a micro-arc oxidation electrolyte.

[0069] The steps of magnesium alloy surface treatment are:

[0070] S11, polishing the AZ91 magnesium alloy with water-resistant sandpaper, rinsing with tap water, and then ultrasonically cleaning with alcohol for 5 minutes to remove surface grease and impurities, then rinsing with deionized water and drying naturally to obtain a pretreated magnesium alloy sample;

[0071] S21, using the pretreated AZ91 magnesium alloy sample as the anode and the stainless steel plate as the cathode, placed in the electrolyte prepared in S11, turned on the cooling water circulation system, used a DC power supply, set the frequency to 500Hz, the duty cycle to 15%, the voltage to within 120V, and the current density to 8A / dm 2 , micro-arc oxidation treatment at 25°C for 15 min;

[0072] S22. After the micro-arc oxidation is completed, the sample is immediately taken out and placed in flowing deionized water for cleaning for 2 minutes to remove the electrolyte residue. Subsequently, it is immersed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. Finally, it is naturally air-dried at room temperature to obtain an AZ91 magnesium alloy with a nanosheet structure film layer on the surface.

[0073] Example 3

[0074] This embodiment provides a micro-arc oxidation electrolyte and a magnesium alloy surface treatment method. The composition of the micro-arc oxidation electrolyte is shown in Table 3:

[0075] Table 3 Composition of Micro-arc Oxidation Electrolyte in Example 3

[0076]

[0077] The preparation method of micro-arc oxidation electrolyte is as follows:

[0078] After adding a film-forming agent, an auxiliary film-forming agent and additives into deionized water, the mixture is fully stirred until they are completely dissolved to obtain a micro-arc oxidation electrolyte.

[0079] The steps of magnesium alloy surface treatment are:

[0080] S11, polishing the AZ31 magnesium alloy with water-resistant sandpaper, rinsing with tap water, and then ultrasonically cleaning with alcohol for 5 minutes to remove surface grease and impurities, then rinsing with deionized water and drying naturally to obtain a pretreated magnesium alloy sample;

[0081] S21, using the pretreated AZ31 magnesium alloy sample as the anode and the stainless steel plate as the cathode, placed in the electrolyte prepared in S11, turning on the cooling water circulation system, using a DC power supply, setting the frequency to 500 Hz, the duty cycle to 15%, the voltage to less than 150 V, and the current density to 6 A / dm 2 , micro-arc oxidation treatment at 15°C for 5 min;

[0082] S22. After the micro-arc oxidation is completed, the sample is immediately taken out and placed in flowing deionized water for cleaning for 2 minutes to remove the electrolyte residue. Subsequently, it is immersed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. Finally, it is naturally air-dried at room temperature to obtain an AZ31 magnesium alloy with a nanosheet structure film layer on the surface.

[0083] Comparative Example 1

[0084] This comparative example provides a micro-arc oxidation electrolyte and a magnesium alloy surface treatment method. The composition of the micro-arc oxidation electrolyte is shown in Table 4:

[0085] Table 4 Composition of the micro-arc oxidation electrolyte of Comparative Example 1

[0086]

[0087] The preparation method of micro-arc oxidation electrolyte is as follows:

[0088] After adding a film-forming agent, an auxiliary film-forming agent and additives into deionized water, the mixture is fully stirred until they are completely dissolved to obtain a micro-arc oxidation electrolyte.

[0089] The steps of magnesium alloy surface treatment are:

[0090] S11, polishing the AZ91 magnesium alloy with water-resistant sandpaper, rinsing with tap water, and then ultrasonically cleaning with alcohol for 5 minutes to remove surface grease and impurities, then rinsing with deionized water and drying naturally to obtain a pretreated magnesium alloy sample;

[0091] S21, using the pretreated AZ91 magnesium alloy sample as the anode and the stainless steel plate as the cathode, placed in the electrolyte prepared in S11, turning on the cooling water circulation system, setting the frequency to 500 Hz, the duty cycle to 15%, using a DC power supply, the voltage controlled within 100 V, and the current density to 5 A / dm 2 , micro-arc oxidation treatment at 20°C for 10 min;

[0092] S22. After the micro-arc oxidation is completed, the sample is immediately taken out and placed in flowing deionized water for cleaning for 2 minutes to remove the electrolyte residue. Subsequently, it is immersed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. Finally, it is naturally air-dried at room temperature to obtain an AZ91 magnesium alloy with a nanosheet structure film layer on the surface.

[0093] Comparative Example 2

[0094] This comparative example provides a micro-arc oxidation electrolyte and a magnesium alloy surface treatment method. The composition of the micro-arc oxidation electrolyte is shown in Table 5:

[0095] Table 5 Composition of the micro-arc oxidation electrolyte of Comparative Example 2

[0096]

[0097] The preparation method of micro-arc oxidation electrolyte is as follows:

[0098] After adding a film-forming agent, an auxiliary film-forming agent and additives into deionized water, the mixture is fully stirred until they are completely dissolved to obtain a micro-arc oxidation electrolyte.

[0099] The steps of magnesium alloy surface treatment are:

[0100] S11, polishing the AZ91 magnesium alloy with water-resistant sandpaper, rinsing with tap water, and then ultrasonically cleaning with alcohol for 5 minutes to remove surface grease and impurities, then rinsing with deionized water and drying naturally to obtain a pretreated magnesium alloy sample;

[0101] S21, using the pretreated AZ91 magnesium alloy sample as the anode and the stainless steel plate as the cathode, placed in the electrolyte prepared in S11, turning on the cooling water circulation system, setting the frequency to 500 Hz, the duty cycle to 15%, using a DC power supply, the voltage controlled within 100 V, and the current density to 5 A / dm 2 , micro-arc oxidation treatment at 20°C for 10 min;

[0102] S22. After the micro-arc oxidation is completed, the sample is immediately taken out and placed in flowing deionized water for cleaning for 2 minutes to remove the electrolyte residue. Subsequently, it is immersed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. Finally, it is naturally air-dried at room temperature to obtain an AZ91 magnesium alloy with a nanosheet structure film layer on the surface.

[0103] Comparative Example 3

[0104] This comparative example provides a micro-arc oxidation electrolyte and a magnesium alloy surface treatment method. The composition of the micro-arc oxidation electrolyte is shown in Table 6:

[0105] Table 6 Composition of the micro-arc oxidation electrolyte of Comparative Example 3

[0106]

[0107]

[0108] The preparation method of micro-arc oxidation electrolyte is as follows:

[0109] After adding a film-forming agent, an auxiliary film-forming agent and additives into deionized water, the mixture is fully stirred until they are completely dissolved to obtain a micro-arc oxidation electrolyte.

[0110] The steps of magnesium alloy surface treatment are:

[0111] S11, polishing the AZ91 magnesium alloy with water-resistant sandpaper, rinsing with tap water, and then ultrasonically cleaning with alcohol for 5 minutes to remove surface grease and impurities, then rinsing with deionized water and drying naturally to obtain a pretreated magnesium alloy sample;

[0112] S21, using the pretreated AZ91 magnesium alloy sample as the anode and the stainless steel plate as the cathode, placed in the electrolyte prepared in S11, turning on the cooling water circulation system, using a bipolar pulse micro-arc oxidation power supply, setting the frequency to 500Hz, the duty cycle to 15%, the voltage to within 350-500V, and the current density to 8A / dm 2 , micro-arc oxidation treatment at 25°C for 15 min;

[0113] S22. After the micro-arc oxidation is completed, the sample is immediately taken out and placed in flowing deionized water for cleaning for 2 minutes to remove the electrolyte residue. Subsequently, it is immersed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. Finally, it is naturally air-dried at room temperature to obtain an AZ91 magnesium alloy with a nanosheet structure film layer on the surface.

[0114] Figure 1 This is the surface morphology of the micro-arc oxidation film layer of AZ91 magnesium alloy in Example 1, where: Figure 1 (a) is the overall surface of the arc oxidation film. Figure 1 (b) Figure 1 (a) The surface morphology of the yellow box area is magnified 150,000 times; Figure 2 This is the surface morphology of the micro-arc oxidation film layer of AZ91 magnesium alloy in Example 2, where: Figure 2 (a) is the overall surface of the arc oxidation film. Figure 2 (b) Figure 2 (a) The surface morphology of the yellow box area is magnified 150,000 times; Figure 3 This is the surface morphology of the micro-arc oxidation film layer of AZ31 magnesium alloy in Example 3, where: Figure 3 (a) is the overall surface of the arc oxidation film. Figure 3 (b) Figure 3(a) The surface morphology of the yellow box area is magnified 150,000 times. Figure 1-Figure 3 It can be seen that after the AZ91 magnesium alloy or AZ31 magnesium alloy is subjected to micro-arc oxidation treatment using the micro-arc oxidation electrolyte and magnesium alloy surface treatment method provided by the present invention, a large number of flaky structures are distributed on the surface of the magnesium alloy. After magnification, it can be seen that the flaky structures are nanosheets with a thickness of less than 100 nm.

[0115] Figure 4 The surface morphology of the micro-arc oxidation film layer of AZ91 magnesium alloy in Comparative Example 1 is shown. In Comparative Example 4, the micro-arc oxidation electrolyte provided by the present invention is not used, and sodium silicate is used as an auxiliary film-forming agent. Figure 4 It can be seen that even if the same magnesium alloy surface treatment method as in Example 1 is used, a nano-sheet structure film layer cannot be generated on the magnesium alloy surface.

[0116] Figure 5 The surface morphology of the micro-arc oxidation film layer of AZ31 magnesium alloy in comparative example 3 is shown in FIG. Figure 5 It can be seen that in Comparative Example 5, the micro-arc oxidation electrolyte provided by the present invention was not used, the concentration of the film-forming agent was low, and the surface treatment of the magnesium alloy adopted a bipolar pulse micro-arc oxidation power supply with a power supply voltage of 350-500V, and a uniform nanosheet structure film layer could not be generated on the surface of the magnesium alloy.

[0117] The AZ91 magnesium alloy having a nanosheet structure film layer on the surface in Example 1 was modified with stearic acid. Figure 6 The contact angles of the AZ91 magnesium alloy with a nanosheet structure film layer on the surface in Example 1 before (a) and after (b) stearic acid modification are shown in FIG. Figure 6 It can be seen that before the AZ91 magnesium alloy with a nanosheet structure film layer on the surface of Example 1 is modified with stearic acid, the micro-arc oxidation film layer is hydrophilic and has a contact angle of about 28°. After being modified with stearic acid, the micro-arc oxidation film layer is hydrophobic and has a contact angle of about 136°. The contact angle becomes larger after modification, indicating that the hydrophilicity of the film layer is reduced and the hydrophobicity is enhanced. The increase in hydrophobicity helps to improve the corrosion resistance and wear resistance of the micro-arc oxidation film layer. It also shows that the magnesium alloy surface treatment method provided by the present invention can form more active sites on the magnesium alloy surface, so that the micro-arc oxidation treated magnesium alloy has the ability to be further functionalized.

[0118] Figure 7 The Tafel polarization curves of the AZ91 magnesium alloy substrate, the AZ91 magnesium alloy with a nanosheet structure film layer on the surface in Example 1, and the AZ91 magnesium alloy with a nanosheet structure film layer on the surface in Example 1 modified with stearic acid in 3.5wt% NaCl aqueous solution. Figure 7It can be seen that compared with the AZ91 magnesium alloy substrate, the corrosion current density of the AZ91 magnesium alloy with a nanosheet structure film layer on the surface in Example 1 is reduced by one order of magnitude, while the corrosion current density of the AZ91 magnesium alloy with a nanosheet structure film layer on the surface in Example 1 modified with stearic acid is reduced by more than two orders of magnitude, which also proves that the corrosion resistance of the magnesium alloy after micro-arc oxidation treatment is enhanced, and the functional modification based on the active sites further enhances its corrosion resistance.

Claims

1. A micro-arc oxidation electrolyte, characterized in that: In terms of concentration, the composition includes: 50-200 g / L of film-forming agent; 20-80 g / L of auxiliary film-forming agent; 1-50 mL / L of additives; and the solvent of the micro-arc oxidation electrolyte is water.

2. The micro-arc oxidation electrolyte according to claim 1, characterized in that: The film former includes an alkali metal hydroxide.

3. The micro-arc oxidation electrolyte according to claim 1, characterized in that: The auxiliary film-forming agent includes ionic fluoride; Preferably, the ionic fluoride includes at least one of sodium fluoride, potassium fluoride and ammonium fluoride.

4. The micro-arc oxidation electrolyte according to claim 1, characterized in that: The additives include polyols; Preferably, the polyol includes at least one of ethylene glycol, propylene glycol, butylene glycol, glycerol and polyethylene glycol.

5. The method for preparing a micro-arc oxidation electrolyte according to any one of claims 1 to 4, characterized in that: The following steps are involved: The components are mixed to obtain the micro-arc oxidation electrolyte.

6. A method for surface treatment of a magnesium alloy, characterized in that: The following steps are involved: S1. pretreating a magnesium alloy workpiece to obtain a pretreated magnesium alloy sample; S2. Using the pretreated magnesium alloy sample as an anode and a stainless steel plate as a cathode, placing them in the micro-arc oxidation electrolyte according to any one of claims 1 to 4, and performing micro-arc oxidation treatment using a DC pulse power supply.

7. The magnesium alloy surface treatment method according to claim 6, characterized in that: In step S2, the voltage of the micro-arc oxidation treatment is 50-150V; And / or, the current density of the micro-arc oxidation treatment is 2-10A / dm 2 .

8. The magnesium alloy surface treatment method according to claim 6, characterized in that: In step S2, the temperature of the micro-arc oxidation electrolyte is 10-30°C.

9. The magnesium alloy surface treatment method according to claim 6, characterized in that: In step S2, the micro-arc oxidation treatment time is 5-30 minutes.

10. A magnesium alloy, characterized in that: The magnesium alloy surface has a nanosheet structure film layer formed by the magnesium alloy surface treatment method according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Method for preparing magnesium alloy corrosion-resistant film layer by utilizing ultra-smooth surface

    CN109989090A

  • Preparation method of magnesium alloy micro-arc oxidation black super-hydrophobic film layer

    CN112458512A

  • MAO-LDH biological composite film layer on surface of magnesium alloy as well as preparation method and application thereof

    CN113638026A

  • Magnesium alloy with super-hydrophobic MAO-LDH composite film layer and preparation method of magnesium alloy

    CN114703529A

  • Preparation method of magnesium alloy surface super-hydrophobic coating

    CN116988120A